2019
DOI: 10.1002/dvdy.101
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rhombomeric interactions reveal roles for fibroblast growth factors signaling in segmental regulation of EphA4 expression

Abstract: Background The basic ground plan of vertebrate hindbrain is established through a process of segmentation, which generates eight transient lineage‐restricted cellular compartments called rhombomeres (r). The segments adopt distinct individual identities in response to axial patterning signals. It is unclear whether signaling between rhombomeres plays a conserved role in regulating segmental patterning during hindbrain development. Results Using tissue manipulations of rhombomeres in chicken embryos, we have un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
(252 reference statements)
0
2
0
Order By: Relevance
“…In the hindbrain, FGF3, FGF8, and RA signaling from hindbrain primordia are essential for setting up the initial identities of hindbrain segments (rhombomeres) by regulating the expression of transcription factors such as Krox20 that control segment identity (Frank & Sela‐Donenfeld, 2019; Parker et al, 2016). In recent studies, rhombomeres 2 and 4 were found to function as temporally dynamic signaling centers that use FGF to regulate the expression of Ephrin type‐A receptor 4 ( EphA4 ) independent of Krox20 in adjacent rhombomeres 3 and 5 (Cambronero et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…In the hindbrain, FGF3, FGF8, and RA signaling from hindbrain primordia are essential for setting up the initial identities of hindbrain segments (rhombomeres) by regulating the expression of transcription factors such as Krox20 that control segment identity (Frank & Sela‐Donenfeld, 2019; Parker et al, 2016). In recent studies, rhombomeres 2 and 4 were found to function as temporally dynamic signaling centers that use FGF to regulate the expression of Ephrin type‐A receptor 4 ( EphA4 ) independent of Krox20 in adjacent rhombomeres 3 and 5 (Cambronero et al, 2020).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…In combination with vhnf1 (Hnf1b) and FGF signalling, these transcription factors specify individual rhombomere identities in the caudal hindbrain (r4-r7) (Parker and Krumlauf, 2017;Sun and Hopkins, 2001;Wiellette and Sive, 2003). In chick embryos, there is evidence for secondary Fgf signalling centres in r2 and r4 that participate in regulating Krox20-independent EphA4 expression (Cambronero et al, 2020). Collectively, this illustrates the presence of crosstalk and regulatory feedback between modules in the GRN.…”
Section: Gene Regulatory Network Underlying Segmentation and A-p Identitymentioning
confidence: 95%